Adding value to neglected and underutilized crop species: Experiences from Kenya, Uganda, Zambia and Zimbabwe - Vernooy, Ronnie; Otieno, Gloria; Adokorach, Joyce; Fusire, Merceline; Munkombwe, Graybill; Mitei, Dalmus; Kimani, Dominic (2023)
This brief presents the research results of the promotion and value addition of selected neglected and underutilized crops in Kenya, Zambia, Uganda, and Zimbabwe. Novel products and value chains were identified, such as (nutritious) composite flours using/mixing amaranth, cassava, millets, yellow (instead of white) maize and sorghum, for particular consumer groups, e.g. adults, adults with diabetes, babies. The production and marketing of these crops and products offers an alternative to the use of maize, whose cultivation is suffering from the impact of climate change across East and Southern Africa.